2022
DOI: 10.3390/rs14051219
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Accuracy and Potential for Improvement of the National Land Cover Database’s Tree Canopy Cover Dataset in Urban Areas of the Conterminous United States

Abstract: The National Land Cover Database (NLCD) provides time-series data characterizing the land surface for the United States, including land cover and tree canopy cover (NLCD-TC). NLCD-TC was first published for 2001, followed by versions for 2011 (released in 2016) and 2011 and 2016 (released in 2019). As the only nationwide tree canopy layer, there is value in assessing NLCD-TC accuracy, given the need for cross-city comparisons of urban forest characteristics. Accuracy assessments have only been conducted for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…The dataset is processed at an annual scale and for 2000, 2005, 2010, and 2015 (referred to as the 4 years thereafter), all of which were used for analyzing the spatial and temporal patterns of TCE. Tree cover derived from 30-m Landsat sensors can be underestimated to varying degrees as indicated by previous studies (Nowak & Greenfield, 2010;Pourpeikari Heris et al, 2022) investigating the accuracy of the National Land Cover Dataset (NLCD). However, the global Landsat VCF tree cover layers used in this study reduce this underestimation as shown in two US cities: San Francisco and Washington selected as examples (Figure S2a,b).…”
Section: Tree Cover Datamentioning
confidence: 97%
“…The dataset is processed at an annual scale and for 2000, 2005, 2010, and 2015 (referred to as the 4 years thereafter), all of which were used for analyzing the spatial and temporal patterns of TCE. Tree cover derived from 30-m Landsat sensors can be underestimated to varying degrees as indicated by previous studies (Nowak & Greenfield, 2010;Pourpeikari Heris et al, 2022) investigating the accuracy of the National Land Cover Dataset (NLCD). However, the global Landsat VCF tree cover layers used in this study reduce this underestimation as shown in two US cities: San Francisco and Washington selected as examples (Figure S2a,b).…”
Section: Tree Cover Datamentioning
confidence: 97%
“…However, there remain considerable false projections among Shrub/Herbaceous and Barren land as these two LULC classes are the most transient land uses in the region due to prevailing forestry practices as well as activities such as solar panel installment, establishment of road construction projects or mining activities. Moreover, land-use classes with similar reflectance in satellite images may lead to classification confusion among some LULC classes, hence there are classification errors associated with these two land uses that can negatively affect the overall accuracy level of projected maps [56,76,77].…”
Section: Discussionmentioning
confidence: 99%
“…Reliance on 1 km spatial resolution satellite data presents limitations to inference in individual cities, though commonly used for global-scale analyses. MODIS may underestimate tree cover in urban and sparsely-treed environments 22,23 and LST may overestimate the effects of trees on human thermal comfort 24 . However, alternative high-resolution commercial urban tree cover products are sparsely available and are costprohibitive for many organizations.…”
Section: Tree Cooling and Water Usementioning
confidence: 99%